Pengembangan Media Pembelajaran SINABA Untuk Meningkatkan Kemampuan Membaca Anak Disleksia di SDN Inklusi Jepara - Nisa, Izatun; Hamidaturrohmah; Rofiqoh, Naili (Universitas Pendidikan Ganesha, 2025)
Appropriate mentoring is the primary key to improving the quality of learning for dyslexic children. One way is by presenting innovative learning media in the accompanying process. This study aims to develop SINABA media to improve the reading skills of dyslexic students in inclusive elementary schools. This research method is research and development with the ADDIE model, which includes five steps: analysis, design, development, implementation, and evaluation. The research subjects were dyslexic children selected based on psychological diagnosis using purposive sampling techniques involving inclusive students. Data collection methods used observation, interviews, and tests. Data collection instruments used questionnaires and test questions. Data analysis techniques used statistical tests using Jamovi and qualitatively. The findings of this research show that the validation results of the SINABA media from media experts were 75%, and material experts were 80%, with a category suitable for use. The results of the media trial showed an increase in the ability to recognize and read letters with an average pretest score of 58.2 and posttest 70.9, with an increase of 12.7 in 11 dyslexic students in the first school. Meanwhile, at the second school, the average pretest score was 60.0, and the posttest score was 73.3, with an increase of 11.6 in six dyslexic students. Therefore, SINABA media has proven effective in improving letter recognition and reading skills in dyslexic students in elementary school.